Think setting up a business is easy? Think again! - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2010)
Entrepreneurship stories are like fairytales. The rags-to-riches stories of college dropouts turned successful multimillionaires provide many an overworked and underappreciated employee with idealism and inspiration: to ditch a life of conventions and to pursue one's passions. But don't be naïve, says Wong Hoong An, chief evangelist officer of the popular local food website, HungryGoWhere.com. There are too many questions to consider, such as 'Can you live with a pittance of a salary for years?' and 'Do you relish change, instability and volatility?'